Energy and Cost Savings through Pumping Stations Rehabilitation. Case Study in Bucharest - Sorin Perju (Proceedings, 2018)
This paper presents the results recorded by upgrading and rehabilitating the pumping stations for an urban water network with a primary goal of diminishing the operation and maintenance costs and a secondary goal of reducing the water losses in the water distribution network. The adopted technical solutions within the structural and functional modifications of the pumping stations have led to both the improvement of hydraulic parameters of the pumping stations and also the improvement of registered energy consumption. The undertaken modifications and transformations within the pumping stations led to significant energy savings and at the same time to important water losses reductions within the distribution network.